Cocrystal Applications in Drug Delivery - Erxleben, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In 2015, the first pharmaceutical cocrystal was approved by the FDA. Since then, the number of cocrystals on the market and in the development pipeline has been slowly but steadily growing. It is now well established that cocrystals are a versatile new approach to oral drug formulation. This Reprint Book is a collection of articles that show the utility of pharmaceutical cocrystals and various aspects of cocrystal research: • Cocrystals as a strategy to modify the physicochemical properties of a drug such as dissolution behaviour, tabletability, and melting point; • Development of new coformers; • Screening studies for multiple cocrystal forms; • Cocrystals in nano-sized drug delivery.